2021
DOI: 10.1126/sciadv.abf4148
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected role for p53 in regulating cancer cell–intrinsic PD-1 by acetylation

Abstract: Cancer cell–intrinsic programmed cell death protein-1 (PD-1) has emerged as a tumor regulator in an immunity-independent manner, but its precise role in modulating tumor behaviors is complex, and how PD-1 is regulated in cancer cells is largely unknown. Here, we identified PD-1 as a direct target of tumor suppressor p53. Notably, p53 acetylation at K120/164 played a critical role in p53-mediated PD-1 transcription. Acetylated p53 preferentially recruited acetyltransferase cofactors onto PD-1 promoter, selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 50 publications
(73 reference statements)
2
21
0
Order By: Relevance
“…The activation of a miRNA, miR-34a, regulates this mechanism [ 46 ]. Studies on the role of p53 in immune evasion are still ongoing, as some studies showed that p53 has a surprising role in the intrinsic PD-1 regulation of cancer cells [ 47 ]. Additionally, although p53 is considered an important factor in PD-L1 regulation, our results exhibit the opposite, as the addition of nobiletin inhibited p53 expression as well as its negative regulator, MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of a miRNA, miR-34a, regulates this mechanism [ 46 ]. Studies on the role of p53 in immune evasion are still ongoing, as some studies showed that p53 has a surprising role in the intrinsic PD-1 regulation of cancer cells [ 47 ]. Additionally, although p53 is considered an important factor in PD-L1 regulation, our results exhibit the opposite, as the addition of nobiletin inhibited p53 expression as well as its negative regulator, MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous mutation of K117, K161, and K162 of mouse p53 (corresponding to K120 and K164 in humans), which destroys acetyl modifications at these sites, completely abolishes p53-mediated cell cycle arrest, senescence, and apoptosis after treatment with IR or genotoxic agents but maintains the ability of p53 to regulate energy metabolism and reactive oxygen species (ROS) production ( Li et al, 2012 ). More recently, we also identified that acetylation of K120 and K164 is critically involved in p53-mediated programmed cell death protein-1 transcription, suggesting a potential link between p53 acetylation and immune modulation in cancer ( Cao et al, 2021 ). In addition, loss of K101 acetylation of p53 impairs solute carrier family 7 member 11 (SLC7A11)-dependent ferroptosis ( Wang et al, 2016b ).…”
Section: The Ptm Code and Its Functional Readout For P53mentioning
confidence: 95%
“…As mentioned in the introduction, HDAC2 is one of the main targets of HBI-8000, providing further evidence that HDAC2 plays a role in the induction of tumor immunity in the tumor microenvironment. Additionally, p53 acetylation showed to play an important role in PD-1 transcription in cancer cells resulting in their growth inhibition independent of the role of PD-1 in the immune system explaining a synergy between HDAC inhibitors and p53 in tumor growth suppression (22). Therefore, HDAC inhibitors appear to play an important role in targeting solid tumors by induction of tumor immunity and directly by acetylation of key components of cancer cells survival.…”
Section: Combination With Checkpoint Inhibitors In Solid Tumorsmentioning
confidence: 98%